UREA DERIVATIVES OF ISOCYANURIC ACID (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Interaction of monomethylol urea with isotsianuric acid has been investigated at different molar rations. Mono-, di- and tris-substituted derivatives of isotsianuric acid have been obtained. The compounds have been studied by IR, PMR spectroscopy and elemental analysis.
Keywords: monomethylol urea; derivatives; isotsianuric acid; IR spectroscopy; PMR spectroscopy; elemental analysis